IMPACTS OF PENSION REFORMS ON THE KENYAN PENSION INDUSTRY - Victoria, Masinde; Olukuru, John (European Scientific Journal, ESJ, 2014)
The emergence of full-fledged reforms in Kenya from the introduction of the Retirement Benefits Authority in1997 has rekindled hopes among the ageing population in Kenya. These reforms are geared towards creating good social welfare conditions for Kenyans. The Kenyan Pension industry remains a significant growth area which needs structural changes in management and governance in order to meet the ever changing scheme member needs. This is what forms the basis of the NSSF Act 2013. In this study the effect of the NSSF Act contribution rate has been examined through use a Contribution rate model. Additionally, Kenyans’ perception towards the yet to be implemented NSSF Act has been observed by use of questionnaire analysis. These reforms are directly linked to the general economic growth of the country. The study asserts that the set 6% contribution is sufficient to meet the welfare conditions of Kenyans. This has been supported by majority of the stakeholders (scheme members, administrators and fund managers among others) however; good implementation strategies need to be put in place in order for the public to realize the good effects of the same. This study therefore seeks to identify the main social welfare reforms put in place, as well as find out the effects and challenges towards implementation of these reforms on the performance of the industry with a critical theoretical look at the NSSF Act 2013.